2015
DOI: 10.1152/ajpheart.00172.2015
|View full text |Cite
|
Sign up to set email alerts
|

The utility of cardiac biomarkers and echocardiography for the early detection of bevacizumab- and sunitinib-mediated cardiotoxicity

Abstract: DS. The utility of cardiac biomarkers and echocardiography for the early detection of bevacizumab-and sunitinib-mediated cardiotoxicity. Am J Physiol Heart Circ Physiol 309: H692-H701, 2015. First published June 19, 2015; doi:10.1152/ajpheart.00172.2015.-The recent introduction of novel anticancer therapies, including bevacizumab (BVZ) and sunitinib (SNT), is associated with an increased risk of cardiotoxicity. However, early identification of left ventricular (LV) systolic dysfunction may facilitate dose mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…However, our data challenge the development of such therapeutic approach because the immediate cardiovascular impact could be disastrous similar to the cardiotoxic effects of antiangiogenic drugs, such as bevacizumab and sunitinib used in cancer therapy. 39 • In this study, we showed that besides its role in the differentiation of vascular smooth muscle cells and in the vascular tone, Notch3 signaling is necessary for the vascular adaptation to hypertension. The consequence of Notch3 signaling impairment is a severe dilated cardiomyopathy that can progress to heart failure.…”
Section: Perspectivesmentioning
confidence: 76%
“…However, our data challenge the development of such therapeutic approach because the immediate cardiovascular impact could be disastrous similar to the cardiotoxic effects of antiangiogenic drugs, such as bevacizumab and sunitinib used in cancer therapy. 39 • In this study, we showed that besides its role in the differentiation of vascular smooth muscle cells and in the vascular tone, Notch3 signaling is necessary for the vascular adaptation to hypertension. The consequence of Notch3 signaling impairment is a severe dilated cardiomyopathy that can progress to heart failure.…”
Section: Perspectivesmentioning
confidence: 76%
“…We have recently shown in patients with lymphoma [51], breast cancer (mainly anthracycline based chemotherapy) [52], and those undergoing treatment with VEGFi [53] that GLS measured by 2D-STE can detect early cardiac damage before a decrease in LVEF is identified. The method has been widely used to monitor cancer patients undergoing chemotherapy [20,[50][51][52][53][54][55][56].…”
Section: Baseline and Monitoring Evaluation Of Oncology Patientsmentioning
confidence: 99%
“…Hence, dysfunctional autophagy is a key player involved in the etiology and/or progression of several cognitive deficitassociated neurodegenerative diseases (Ghavami, et al, 2014). Others and we have previously shown that sunitinib had both positive and negative effects on autophagic status in cancer cells (Abdel-Aziz, et al, 2014, Bordun, et al, 2015, Lopergolo, et al, 2014, Santoni, et al, 2013. In spite of this, the effects of sunitinib on both apoptotic and autophagic machineries within a "neurocognitive" frame have not been addressed yet.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Indeed, cognitive deficits associated with several neurodegenerative diseases as Alzheimer's disease as well as exposure to neurotoxic insults triggered by chemotherapeutics and traumatic brain injury were shown to be mediated via activation of the "executioner" apoptotic machinery ultimately resulting in synaptic malfunction and neuronal cell loss (Walker and Tesco, 2013). In this context, the cyotoxic effects of sunitinib in both cancer and non-cancerous cells as cardiomyocytes is mediated via inducing apoptosis (Abdel- Aziz, et al, 2014, Bordun, et al, 2015. Autophagy (or self-eating) is an evolutionarily conserved recycling process.…”
Section: Accepted Manuscriptmentioning
confidence: 99%